Keparahan karies yang tidak dirawat pada anak berdasarkan indeks PUFA/pufa - Sri Nurul Aini Siregar; Molek Molek; Kelvin Kelvin (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2019)
Dental caries is one of the problems of dental and oral diseases that are mostly suffered by school children throughout the world, including Indonesia. School-age children especially elementary school children are vulnerable to caries. If dental caries are untreated it will cause pulpitis, ulceration, fistulas and absceses. The main objective of this study was to determine the severity of dental caries in children in class 1, 2 and 3 in Parulian 2 Elementary School Medan based on the PUFA / pufa index. This research was conducted using descriptive methods. The study population was all students in class 1st, 2nd and 3rd of Parulian 2 Elementary School Medan, which amounted to 155 students / i. The research sample is 100 respondents who have met the inclusion criteria. The results showed that the mean severity of caries was not treated and caused an open pulp (P p) of 1.54; ulser (U / u) 0.06; none causes a fistula (F / f) 0.00; absceses (A / a) 0.07. Caries severity was not treated based on the PUFA / Pufa index (1.7). Most severity in 7-year-old students and male sex. The conclusion of this study is a description of the severity of untreated caries at children in class1st, 2nd and 3rd children in Parulian 2 Elementary School Medan based on the PUFA / pufa index is poor.